Report on: Current Status and Overview of Farm Mechanization in Uzbekistan – A Review - Devkota Wasti, Mina Kumari; Nurbekov, Aziz; Devkota, Krishna (International Center for Agricultural Research in the Dry Areas, 2022)
Mechanization covers all field works in agriculture, including processing technologies; it can be started from hand tools to more sophisticated and motorized agricultural machinery. Uzbekistan’s agriculture is one of the sectors of the economy which is the most regulated by the state. The markets for many types of agricultural products and production resources and services for the sector are not well developed. Hence this sector is in desperate need of reform. Modern agriculture requires a wide range of technology, knowledge, and skills used by farmers and agri businesses, from operating modern machinery and equipment in open fields and greenhouses to maintaining minimum safety, hygiene, and quality standards in all stages of production, harvesting, post-harvesting, processing, and marketing. Today, agricultural enterprises have a total of 255,586 units of mainly 20 different types of agricultural machinery. 65% of available agricultural machinery is concentrated in commercial companies that provide agricultural machines for fieldwork during crop growing season, 8% in newly established clusters, while 27% belongs to farms and Shirkat farms. This report discusses challenges faced in the machinery sector and technology infrastructure, including technical training, machinery dealer support, repair and maintenance, and suggestions for the future.